1986
DOI: 10.1289/ehp.8665229
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of the testicular toxicity of phthalate esters.

Abstract: Di(2-ethylhexyl) phthalate (DEHP) produced seminiferous tubular atrophy and reductions in seminal vesicle and prostate weight in 4-week-old, but not in 15-week-old rats. Di-n-pentyl phthalate (DPP) did produce atrophy in the older rats but this developed more slowly than in young animals. Coadministration of testosterone or gonadotrophins did not protect against phthalate-induced testicular toxicity but did partly reverse the depression of seminal vesicle and prostate weight. Secretion of seminiferous tubule f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
59
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(62 citation statements)
references
References 24 publications
(36 reference statements)
3
59
0
Order By: Relevance
“…[1985a,1985b]; Plonait et al [1993] Intestinal absorption occurs more readily in rodents than in primates, presumably because of higher concentrations of lipases [Rhodes et al, 1986]. Young rodents absorb DEHP/MEHP to a greater degree than adults [Gray and Gangolli, 1986]. Once absorbed, DEHP is widely distributed throughout the body, with fat, the lungs, absorptive organs (gastrointestinal tract), and excretory organs (liver, kidneys) being the major initial repositories.…”
Section: Disposition and Metabolism Of Dehpmentioning
confidence: 99%
“…[1985a,1985b]; Plonait et al [1993] Intestinal absorption occurs more readily in rodents than in primates, presumably because of higher concentrations of lipases [Rhodes et al, 1986]. Young rodents absorb DEHP/MEHP to a greater degree than adults [Gray and Gangolli, 1986]. Once absorbed, DEHP is widely distributed throughout the body, with fat, the lungs, absorptive organs (gastrointestinal tract), and excretory organs (liver, kidneys) being the major initial repositories.…”
Section: Disposition and Metabolism Of Dehpmentioning
confidence: 99%
“…It was reported that exposure to DEHP causes testicular atrophy with spermatogenic disturbance (SD) in mice and rats [9][10][11][12][13][14]. Others have shown that DEHP is rapidly metabolized into mono-2-ethylhexyl phthalate (MEHP), and that MEHP induces spermatogenetic disturbance mainly via oxidative stress [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Studies on rodents involving large amounts of phthalates have shown damage to the liver and testes and birth defects (Gray, Butterworth, Gaunt, Grasso, & Gangolli, 1977). Mono-(2-ethylhexyl) phthalate (MEHP), a metabolite of DEHP, ultimately may be the active testicular toxicant and may increase the liver weight in rats (Gray & Beamand, 1984;Gray & Gangolli, 1986). In addition, a recent study showed that the di-butyl phthalate (DBP) or its metabolite mono-butyl phthalate (MBP) suppresses steroidogenesis by fetal-type Leydig cells in primates as in rodents (Ema, Murai, Itami, & Kawasaki, 1990;Hallmark et al, 2007;Parks et al, 2000).…”
Section: Introductionmentioning
confidence: 99%